2022
DOI: 10.1007/s10526-022-10166-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on survival of Australian entomopathogenic nematodes and their virulence against the Queensland fruit fly, Bactrocera tryoni

Abstract: Entomopathogenic nematodes (EPNs) are commonly used biocontrol agents of insect pests, with a wide range of commercially available isolates targeting specific pests. New isolates are, however, required to improve pest control across a wider range of environmental conditions for target pests, including emerging threats. We assessed the effect of temperature on survival and virulence of 17 Australian isolates of five EPN species (Heterorhabditis bacteriophora, Heterorhabditis indica, Heterorhabditis marelatus, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…However, studies investigating the differences in the efficacy of EPN after storage at different temperatures for certain periods, as done in this study, are very few (Aryal et al, 2022). Similar to the present study is the study by Aryal et al 2022, who reported using the EPN species isolated from Australia; H. bacteriophora, H. zealandica, H. indica and S. felitae. According to their results, H. zealandica had the highest virulence at 25 and 30°C.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, studies investigating the differences in the efficacy of EPN after storage at different temperatures for certain periods, as done in this study, are very few (Aryal et al, 2022). Similar to the present study is the study by Aryal et al 2022, who reported using the EPN species isolated from Australia; H. bacteriophora, H. zealandica, H. indica and S. felitae. According to their results, H. zealandica had the highest virulence at 25 and 30°C.…”
Section: Discussionsupporting
confidence: 79%
“…These studies mostly focused on the virulence effects of EPN on different hosts at different temperatures (Nimkingrat et al, 2013;Ulu & Susurluk, 2014;Baimey et al, 2015;Yan et al, 2020). However, studies investigating the differences in the efficacy of EPN after storage at different temperatures for certain periods, as done in this study, are very few (Aryal et al, 2022). Similar to the present study is the study by Aryal et al 2022, who reported using the EPN species isolated from Australia; H. bacteriophora, H. zealandica, H. indica and S. felitae.…”
Section: Discussionmentioning
confidence: 99%
“…Nematodes that are in anabiosis are more tolerant of extreme temperatures than nematodes that are active under these unfavorable conditions [124]. Nematode strains that are used in the biocontrol of pests of living plants are active at temperatures between 10 • C and 30 • C [146][147][148].…”
Section: Temperaturementioning
confidence: 99%